GAMBARAN TINGKAT KEPATUHAN PESERTA PROLANIS DIABETES MELITUS TIPE 2 YANG MENGGUNAKAN MASKER DAN HAND SANITIZER SELAMA PANDEMIK COVID-19 DI KLINIK IMAN MEDAN - BELLA DWI FITRI; SHAHRUL RAHMAN (JURNAL ILMIAH SIMANTEK, 2023)
COVID-19 is a pandemic outbreak that emerged in December 2019. This virus can transmit through droplets from sufferers. For this reason, it is necessary to be vigilant by complying with early precautions for the transmission of the COVID-19 virus, namely by using masks and hand sanitizers. Diabetes Mellitus type 2 is a comorbid disease which is one of the risk factors for contracting COVID-19 and is very susceptible to occur in elderly sufferers. PROLANIS is a program that educates people with Type 2 Diabetes Mellitus. To determine the level of compliance of PROLANIS Diabetes Mellitus type 2 participants who use masks and hand sanitizers during the COVID-19 pandemic at the IMAN Medan Clinic.This type of research is a descriptive study with a case control design, namely a study using the case group and the control group. By taking the sample using consecutive sampling where the sample selection by determining the subjects who meet the research criteria are included in the study until a certain time, so that the number of respondents can be fulfilled. The results showed that adherence was higher in using Maker and Hand Sanitizer in the PROLANIS group and the Control group more in the female sex than the male gender. Based on the level of education, high adherence is obtained at the high school level, this is because education> 9 years is much more obedient 75.0% compared to <9 years 40.5%. High adherence in the control group adherence to using masks and the use of Hand Santizer at the age of 20-39 more. Meanwhile, the PROLANIS participants were more obedient to using masks and using Hand Sanitizers at the age of 61-70 years. The PROLANIS program is very useful for elderly participants who have comorbid diseases to educate them about complying with health protocols.